THE EFFECT OF REINVENTING POTENTIAL AND FINANCIAL INDEPENDENCE ON THE ENTREPRENEURS CHARACTER OF MILLENNIALS THROUGH SOCIAL MEDIA IN THE ERA MARKETING 4.0 - Adnan Adnan; Aiyub Yahya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The study presents the results of the impact of reinventing potential and financial independence on the entrepreneur character of millennial generation through social media in the era marketing 4.0. The data were obtained from a survey of 448respondents(student) from fourdepartement of Faculty Economic and Bussiness Malikussaleh University in Indonesia. The following statistical methods were used: descriptive statistics and structural eqution modelling analysis. The study found that reinventing potential, financial independence and social media has a significant effect on the entrepreneurial character of the millennial generation in IndonesiaAnother finding: Social media did not moderate the relationship between reinventing potential and the entrepreneurial character of the millennial generation, but social media was found to moderate the relationship between financial indenpendence and the entrepreneurial character of the millennial generation in the marketing era 4.0.